The development of mass assessment and taxation of real estate as a basis for increasing the source income of the local self-government units of the Republic of Srpska - Biljana Srdić Gojković; Dragan Stanković (Economic Themes, 2024)
Municipal budgets represent the basis of the development of an area with a certain number of inhabitants. The quality of life of the population will depend on the size of the budget and the potential for the development of the municipality. The budget system of the Republic of Srpska includes the budget of the Republic, the budgets of municipalities and cities, and the budgets of funds. The local selfgovernment units form part of the overall public finances of the Republic of Srpska and they play an important role in maintaining the fiscal stability and responsibility in the Republic of Srpska as a whole, but also individually from the aspect of the quality of life. Public finances of the local self-government units make up 15% of the total public finances of the Republic of Srpska. Therefore, from the aspect of the stability of public finances, it is very important to establish a database that will contain the exact number of immovable properties on the basis of which the local self-government units of the Republic of Srpska would increase the income item from property tax, and therefore the total budgets, especially bearing in mind their financial problems. That is why it is necessary to analyze with special attention the possibility of increasing the income of the local self-government units of the Republic of Srpska.
Keywords: H70; H71; H72; F40; 330; property tax; source income of LGUs; fiscal stability ofLGUs